2016
DOI: 10.1111/boer.12068
|View full text |Cite
|
Sign up to set email alerts
|

The Forecasting Performance of Setar Models: An Empirical Application

Abstract: The aim of this paper is to evaluate the forecasting performance of SETAR models with an application to the Industrial Production Index (IPI) of four major European countries over a period which includes the last Great Recession. Both point and interval forecasts are considered at different horizons against those obtained from two linear models. We follow the approach suggested by Teräsvirta et al. (2005) according to which a dynamic specification may improve the forecast performance of the nonlinear models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Thus, the politicians need the scientific reliable information of the related indicators in the country. Time Series Analysis is a suitable method that provides us to reach this information [16]. In this article, we forecast the monthly data of the IPI series that is one of the most important economic indicators in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the politicians need the scientific reliable information of the related indicators in the country. Time Series Analysis is a suitable method that provides us to reach this information [16]. In this article, we forecast the monthly data of the IPI series that is one of the most important economic indicators in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the models are re-specified at the end of each year, such that the first specification is based on data up to fourth quarter of 2005 and the last specification on data up to fourth quarter of 2013. This approach is inspired to the recommendations of Teräsvirta et al (2005) and Boero and Lampis (2016), who suggest that frequent model re-specification increases the forecast accuracy of nonlinear models. Moreover, this procedure allows us to take into account the structural breaks occurred between 2008 and 2009 when the Great Recession hit Spanish economy severely.…”
Section: Empirical Analysis and Forecastmentioning
confidence: 99%
“…The forecasting exercise is performed on 1-step-ahead and 4-steps-ahead point forecasts using a recursive scheme with an expanding window to approximate a genuine forecasting environment. This approach is based on the recommendations of Teräsvirta et al (2005), Ferrara et al (2012) and Boero and Lampis (2016), who found it very convenient when the forecasting accuracy of nonlinear models is considered. In the next section, we present the statistical information available for the Basque Country, and in the third section, we briefly describe the models estimated and compare the forecasting accuracy of our models.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the evaluations, they reported that the best modeling for the time series in question was the AAR-SETAR modeling. Boero and Lampis (2016) in [3] conducted a study for 4 major European countries and applied SETAR modeling by using Industrial Production Index (IPI) values, and investigated the belief that claimed that the dynamic determination process increased the prediction performance (Terӓsvirta et al (2005)). However, the literature is not rich in terms of the properties of the sampling on this model group and in terms of test statistics (Hansen, 1997).…”
Section: Introduction and The Literaturementioning
confidence: 99%